Chapter 3 The Future Isn't What It Used to Be! Revisiting the Changing World of Work After Covid- 19 - Hooley, Tristram (Taylor & Francis, 2023)
This chapter explores the future of work. It argues that while predicting the future is very difficult, this has not prevented a wide variety of commentators from seeking to make such predictions. Covid-19 has resulted in a substantial reimagining of the future of work. Prior to the pandemic, the future was imagined as one of automation, digital technology, globalisation, and the reduction in the utility of human beings unless they could increase their adaptability and flexibility. After the pandemic, the future of work is characterised in terms of a shift to remote working practices, accelerating technological change, growing unemployment, and inequality. Such changes have led commentators to call for increased government engagement in the economy and the workplace, and for new thinking and investment from businesses to manage the changes. Such shifts and changes, if they come to pass, require an active and robust response from career educators. Educators should encourage students to view predictions about the future critically, to recognise their contingency and support them to take both individual and collective action to shape the future.